2018
DOI: 10.2147/copd.s176065
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 2011 and 2017 Global Initiative for Chronic Obstructive Pulmonary Disease (GOLD) guidelines on allocation and pharmacological management of patients with COPD in Taiwan: Taiwan Obstructive Lung Disease (TOLD) study

Abstract: BackgroundThis nationwide study was performed to evaluate the evolution of distributions of patients with COPD according to the 2011 and 2017 Global Initiative for Chronic Obstructive Pulmonary Disease (GOLD) guidelines and to assess the concordance between the prescribed medications and the pharmacological management recommended by the two distinct classification systems in Taiwan.Subjects and methodsData were retrospectively retrieved from stable COPD patients in 11 participating hospitals across Taiwan. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 36 publications
8
45
0
Order By: Relevance
“…The adherence rate was almost three times higher in patients classified A/B GOLD groups when compared to those classified C/D (Table 5). This finding is partially in line with those reported in some related studies [6,9,13] (Appendix A). First, after adjusting for age, sex, smoking habits, number of exacerbations, control of symptoms, and health service use, Maio et al [6] showed that group D patients, compared to the ones in group A, are significant protective factors for the lack of prescriptive appropriateness (OR: 0.05).…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'supporting
confidence: 93%
See 1 more Smart Citation
“…The adherence rate was almost three times higher in patients classified A/B GOLD groups when compared to those classified C/D (Table 5). This finding is partially in line with those reported in some related studies [6,9,13] (Appendix A). First, after adjusting for age, sex, smoking habits, number of exacerbations, control of symptoms, and health service use, Maio et al [6] showed that group D patients, compared to the ones in group A, are significant protective factors for the lack of prescriptive appropriateness (OR: 0.05).…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'supporting
confidence: 93%
“…Yet, the Tunisian pulmonologists' adherence rates were intermediate compared to those reported in similar studies (Table 1S). The adherence rates varied from 0.2 [43] to 61.5% [16] in group A, from 0.2 [43] to 43.9% [9] in group B, from 0.0 [43] to 81.5% [10] in group C, and from 4.6 [10] to 96.2% [41] in group D. To summarize, COPD patients continue to be treated in the wrong way, signifying that the GOLD PTGs are not being completely utilized [13]. This frequent pattern is not specific to the developing countries, but it is rather an international issue (Table 1S).…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 94%
“…Of these, the 2017 revision had particular importance because it refined the previous ABCD assessment considering patient symptoms [ 5 , 6 ], combined with the history of exacerbations, excluding spirometry grading and modifying the pharmacological recommendations [ 1 ]. Although the COPD guidelines are important for the management of the disease [ 4 ], in a number of countries, low levels of adherence to the guideline recommendations were recorded among doctors treating different patient cohorts [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], often with overtreatment with inhaled corticosteroids (ICS) [ 13 ]. According to the World Health Organization (WHO) [ 15 ], factors influencing pulmonologist adherence to the guidelines are very complex, related not only to the physician, but also to the patient, disease, and/or social aspects [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the evolvement of the GOLD recommendations over the years mirrors the evolvement of our understanding of the disease. Before the 2011 update of the GOLD recommendations, therapy recommendations were based primarily on lung-function values 53 . Current treatment recommendations are based on a combination of lung function, symptoms and number of exacerbations in the previous year.…”
Section: Gold 1 Versus Gold 4 Copdmentioning
confidence: 99%